Farmers of the southern Caribbean of Costa Rica: Socioeconomic, productive, and commercial characterization - Harvey-Chavarría, Marianita; Estrada-León, Raciel Javier (Agronomía Mesoamericana, 2023)
Introduction. In Costa Rica, the agricultural sector is one of the most diverse, it presents, a high socioeconomic variability. The canton of Talamanca harbors a strong economic lag and it is necessary the generation of productive alternatives. Objective. To characterize the socioeconomic, productive, and commercial level of the South Caribbean farmers. Materials and methods. An exploratory and descriptive study was carried out in the districts of Cahuita, Bratsi, and Sixaola of Talamanca from 2019 to 2021. A sample size was determined with a confidence level of 95%. A structured questionnaire with twenty-seven questions was designed for farmers, and eight for heads of government institutions in the area. Surveys were applied to 155 farmers and 33 representatives of institutions and organizations. Farmers were classified through hierarchical cluster analysis and discriminant analysis, continuous quantitative socioeconomic variables were used. Results. Four types of farmers were identified, 1) subsistence farmers (ATS, 7.10 %), 2) small (ATP, 23.23 %), 3) medium (ATM, 41.29 %), and 4) large (ATG, 28.39 %), with significant statistical differences (p<0.05, χ2<0.05) between their study variables. Regarding agro-industry, it was identified that 77.91 % did not industrialize their products, due to lack of market (14.68 %) and lack of resources (14.37 %) as the main reasons. Conclusion. The agricultural activity is characterized by family farming. Plantain, cocoa, and bananas are produced; however, the diversity of crops and fruit trees represents a high potential for the development of agro-industry.